(untitled) (Research, Society and Development, 2021)
Invasive cervical resorption is an aggressive pathological process that affects the dental cervical region, of destructive and reparative nature. Knowledge of its evolutionary phases, a correct diagnosis and classification are essential for an adequate treatment plan. The present study aims to perform a literature review on invasive cervical resorption, its clinical aspects and therapeutic options. An electronic search was conducted in PubMed databases using the MeSH terms: "root resorption", "endodontics" and "management", and the boolean operator "AND". The studies showed that the clinical and radiographic aspects of invasive cervical resorption vary according to its evolutionary stage. A careful clinical evaluation is essential for a correct differential diagnosis, and the radiographic exams of choice are cone beam computed tomography or nano computed tomography. Its treatment consists of internal approach, external approach, intentional reimplantation, follow-up or exodontia. Although invasive cervical resorption is considered a rare pathology, its aggressive nature can culminate in tooth loss. Thus, knowledge about it is essential for a correct clinical conduct, always aiming at the functional and aesthetic maintenance of the affected tooth.